Participation of adolescents in the Family Health Strategy from the theoretical-methodological structure of an enabler to participation - Roberta Peixoto Vieira; Sílvia Helena Pereira Gomes; Maria de Fátima Antero Sousa Machado; Italla Maria Pinheiro Bezerra; Caroline Antero Machado (Universidade de São Paulo, 2014)
OBJECTIVE: to evaluate the participation of adolescents in the Family Health Strategy, from the theoretical-methodological structure of an enabler to participation.METHOD: a quantitative study, conducted from December of 2010 to March of 2011, with 213 professionals in the FHS in the region of Cariri-Ceará-Brazil. Data were collected through a questionnaire and organized in SPSS 18.0.RESULTS: the level of normative participation becomes manifest beginning with the adolescent search for health services, motivated by disease (77.9%). Normative participation + independence appear when they seek prenatal care and family planning. Emancipatory participation was identified by the frequency of adolescents in group activities, in the schools, and a move in the direction of the level of transformative participation was observed.CONCLUSION: in this context, it is understood that there exists a need to stimulate the participatory process of the adolescents for a change in health promotion in this group.